Supplementation of high-quality fresh forage to lambs fed a total mixed ration increased in vitro ruminal fermentation and digestibility - Pérez-Ruchel, Analía; Repetto, José Luis; Cajarville, Cecilia (Frontiers in Animal Science, 2023)
The supplementation of fresh alfalfa into the diet of growing lambs fed with decreasing levels of a total mixed ration (TMR) was studied for its effect on in vitro ruminal fermentation activity. Twenty-four catheterized lambs [25.2 ± 3.67 kg body weight (BW)] were assigned to one of the following treatments: “TMR100”—TMR ad libitum; “TMR75’” and “TMR50”—TMR at 0.75 and 0.50 of potential intake, respectively, supplemented with alfalfa; and ‘TMR0’—only alfalfa ad libitum. In vitro gas production kinetics and true digestibility (IVTD) were evaluated using the rumen liquid as inocula. Ruminal pH values and NH3-N and volatile fatty acid concentrations were studied at the same time as inocula extraction. As the amount of alfalfa in the diet increased—by decreasing the level of TMR—in vitro gas production, ruminal pH values, NH3-N concentrations, and acetic acid proportions linearly increased (p = 0.005, 0.008, 0.004, and 0.018, respectively). IVTD tended to linearly rise (p = 0.083) and the fermentation rate (p = 0.004) and propionic acid proportion (p< 0.001) linearly decreased. We conclude that the increase in the level of fresh alfalfa resulting from the decrease in TMR levels in lambs’ diet positively impacted rumen fermentation activity and in vitro digestibility through the promotion of a suitable environment for ruminal microbiota.